The Level of Physical Fitness at SSB Citra Panciro Jaya - Ridwan, Andi; Ihsan, Andi; Adil, Ahmad (Sains Global Institut, Indonesia, 2023)
The purpose of the study is: To determine the level of physical fitness in football games at SSB Citra Panciro Jaya. The sample of this study was all football players at SSB Citra Panciro Jaya with a total of 30 students. The data collection method uses the test method. The data was analyzed using percentage descriptive analysis and analyzed with the help of SPSS program version 22. The results showed that: The level of physical fitness in SSB Citra Panciro Jaya was moderate with a percentage of 17 players (56.67%). Or the average TKJI score of 16.80 points which includes medium scores.